Analisis User Interface Terhadap Kemudahan Pengguna Website E-Learning STIKOM Bali - Ni Putu Linda Santiari; I Gede Surya Rahayuda (Seminar Ilmiah Nasional Teknologi, Sains, dan Sosial Humaniora (SINTESA), 2019)
ABSTRACTWebsites are very important in all fields, especially for an organization or company. The website has various types and e-learning is one type of website. E-learning has the meaning as the delivery of material and methods of education that use information technology for teaching, learning, training or acquiring knowledge anytime and anywhere. STIKOM Bali is one of the universities where the lecture process has been using e-learning. One important component that can improve the usability of e-learning is the appearance of the interface or commonly referred to as the user interface. The STIKOM Bali e-learning interface is important for users to improve user experience. Testing is done in two stages, namely usability testing and testing of aspects of the user interface. From the usability test results obtained usability problems of the STIKOM Bali e-learning website are low seen from the results of the heuristic evaluation where aspects H4, H6, H9 while H1, H2, H3, H5, H7, H8, H10 have low usability problems. In testing aspects of the user interface good results are obtained.Keywords: website, user, interfaceABSTRAKWebsite sangatlah penting dalam segala bidang terutama untuk sebuah organisasi ataupun perusahaan. Website memiliki berbagai jenis dan e-learning merupakan salah satu jenis dari website. E-learning mempunyai pengertian sebagai penyampaian materi dan metode pendidikan yang menggunakan teknologi informasi untuk keperluan pengajaran, pembelajaran, pelatihan atau memperoleh pengetahuan kapan pun dan di mana pun. STIKOM Bali merupakan salah satu sekolah tinggi yang proses perkuliahannya sudah menggunakan e-learning. Salah satu komponen penting yang dapat meningkatkan ketergunaan e-learning adalah segi tampilan antar muka atau yang biasa disebut dengan user interface. Tampilan antar muka e-learning STIKOM Bali penting bagi penguna untuk meningkatkan pengalaman pengguna. Pengujian dilakukan dua tahap yaitu pengujian usability dan pengujian aspek user interface. Dari hasil pengujian usability diperoleh Permasalahan usability website e-learning STIKOM Bali rendah dilihat dari hasil evaluasi heuristik dimana aspek H4, H6,H9 sedangkan H1,H2,H3,H5,H7,H8,H10 permasalahan usability rendah. Pada pengujian aspek user interface diperoleh hasil baik.